Pendidikan Islam Masa Penjajahan Jepang di Sambas, Indonesia - Aslan (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
Since the Dutch and Japanese colonial era, the development of Islamic educational institutions has shifted in various paradigms. During the Dutch period, educational discrimination occurred, while the discrimination was abolished in Japan. In response to this reality, the study aims to explore the Japanese policy system toward Islamic education in Indonesia and to describe their policy systems for the people of Sambas, West Kalimantan. Grounded in a literature study, this articles provides a thorough analysis of book references, nationally and internationally reputed journals, and resources relating to Islamic education during the Japanese colonization in Indonesia. Findings of the study expose that firstly, the Japanese policy system in Indonesia demonstrated the vision of Nipponization embedded in a wide array of sectors, including education. The Japan’s goal was to be the leader of the Greater Asia by influencing Indonesian society with an education system designed by Japan. Secondly, concerning the policy system in Sambas, Japan was more open to the Sambas community for the key weakness of Sambas was religious issues. This openness intended to promote Islamicorganizations to gain support as leaders of the Greater Asia. To succeed this mission,educational institutions eroded any discrimination by no longer looking at diversity, as agoal to incorporate the Nipponization-based contents.